Changing family relationships and mental health of Chinese adolescents: the role of living arrangements. (September 2020) - Liu, Y.; Ge, T.; Jiang, Q.
Abstract: Objective: This study examined the association between changing family relationships (marital relationships and parent-child relationships) and adolescents' mental health in transitional China. It further explored the potential moderating role of living arrangements in the abovementioned associations. Study design: The study design used in the study is a longitudinal study. Methods: Data were derived from wave 1 (academic year: 2013–2014, grade 7) and wave 2 (academic year: 2014–2015, grade 8) of the China Education Panel Survey (CEPS). We used fixed-effects models in the longitudinal data analysis (N = 7237). Results: Descriptive analysis indicated significant changes in both adolescents' mental health and self-reported family relationships during the transition from grade 7 to grade 8. The fixed-effects models showed that high marital quality and close parent-child relationships improved the mental health of adolescents. Interaction analysis suggested that paternal living arrangements significantly moderated the association between the father-child relationships and adolescents' mental health: effects of the father-child relationships were weaker among those living away from their biological fathers than among those living with their biological fathers. Conclusions: Family relationships play an important role in shaping Chinese adolescents' psychological status. However, the effect of the father-child relationships varies based on the paternal living arrangements. This finding highlights the importance of considering the context in examining the effects of family relationships on adolescents' well-being. Highlights: In the transition from grade 7 to grade 8, adolescents' mental health and family relationships change significantly. Marital quality of parents is positively associated with mental health of adolescents. Quality of parent-child relationships is positively associated with mental health of adolescents. Links between father-child relationships and adolescents' mental health differ by paternal living arrangements.